Thermographic studies of outer target heat fluxes on KSTAR. (August 2017) - Lee, H.H.; Pitts, R.A.; Kang, C.S.; Oh, S.T.; Bak, J.G.; Hong, S.H.; Wi, H.M.; Kim, Y.S.; Kim, H.S.; Seo, D.C.; Kim, H.T.; Kim, K.M.
Highlights: The divertor infra-red thermography system for outer divertor heat flux profile measurement on KSTAR is introduced. The first measured Inter-ELMs outer divertor heat load profiles in KSTAR plasmas agree well with the recently proposed power decay length scaling. It is also shown that the resonant magnetic perturbations fields can actively control the strike point splitting pattern of the divertor heat flux. Abstract: A new infra-red (IR) thermography system with high spatial resolution has been installed on KSTAR and is now mainly applied to measure the outer divertor heat load profile. The first measurement results of the outer divertor heat load profiles between ELMs have been applied to characterize the inter-ELMs outer divertor heat loads in KSTAR H-mode plasmas. In particular, the power decay length ( λq ) of the divertor heat load profile has been determined by fitting the profile to a convolution of an exponential decay and a Gaussian function. The analysis on the power decay length shows a good agreement with the recent multi-machine λq scaling, which predicts λq of the inter-ELMs divertor heat load to be ∼1  mm under the standard H-mode scenario in ITER. The divertor IR thermography system has also successfully measured the strike point splitting of the outer divertor heat flux during the application of resonant magnetic perturbation (RMP) fields. In addition, it has provided a clear evidence that the strike point splitting pattern depends on the RMP fields configuration.